The Dilemma of Islamic Education and Prostitution Life - Waza Karia Akbar; Yuhelna Yuhelna; Sri Rahmadani (Journal of Education on Social Science (JESS), 2021)
The Minangkabau society is famous for the tradisional philosophy of adat basandi sarak, sarak basandi kitabullah (ABS-SBK). Education and religious values have been passed down from one generation to another. However, it is still not going well. It is seen with the many women who are trapped in negative terms. They are very weak people in the economy and religious education. The goal to be achieved in this study in find out the causes of Minangkabau women who are continually involved in the world prostitution. The focus of this research is the woman in the localization of the goddess Aro, West Sumatera. The method used by researchers is qualitative with case studies in the Andam Dewi. The findings suggest that those involved in prostitution were women aged 17-27 years old because of the economic factors and religious knowledge are very weak. Other findings also show the weak role of Mamak in Minangkabau in monitoring its ministry.